Военно-патриотическое воспитание советской молодежи - Бублик Л. А.; Андрющенко Е. Г.; Ковалев В. Н.; Колычев В. Г.; Средин Г. В. Геннадий Васильевич (Москва, Воениздат, 1983)
Авт. указаны на обороте тит. л.